Comparison Between International Federation of Gynaecology and Obstetrics Guidelines Versus Conventional Method for the Treatment of Third Stage Labour (Medical Forum Monthly, 2020)
Objective: To observe the comparison between International Federation of Gynaecology and Obstetrics guidelines versus conventional method for the treatment of third stage labour.Study Design: Quasi experimental studyPlace and Duration of Study: This study was conducted in Gynaecology and Obstetrics Department at Pak Red Crescent Medical & Dental College, Dina Nath, Kasur from July 2019 to December 2019.Materials and Methods: It was a quasi experimental study and consisted of a total 100 labouring women after gestational period of 28 weeks till 41 weeks having spontaneous labour or augmented labour. Fifty women were managed conservatively and 50 women managed by FIGO guideline.Results: The patients were divided into 2 groups, 50 in each group. Group A was managed by FIGO guideline and group B was managed by conventional method. As compared to group A, in group B the risk of PPH, need of blood transfusion was significantly high and there was significant reduction in haemoglobin percentage after delivery in group B as compared to group A. Other side affects like headache, nausea, vomiting are also higher in group B as compared with group A.Conclusion: It is concluded that FIGO guidelines are more efficacious in prophylaxis of PPH. The conventional method of third stage of labour with minimal side effects and can safely be administered to hypertensive patients.